Effects of the scope of practice on family physicians: a systematic review - Zomahoun, Hervé Tchala Vignon (BMC Fam Pract, 2021)
BACKGROUND: Family medicine is a branch of medicine that manages common and long-term illnesses in children and adults. Family physicians in particular play a major role and their scope of practice is expected to impact patient and population. However, little is known about its impact on physicians. We aimed to assess the effects of scope of practice on family physician outcomes. METHODS: We performed a systematic review that we reported using PRISMA guidelines. For the inclusion criteria, any study exploring an association between the scope of practice and physician outcomes was considered. Three bibliographic databases Medline, Embase, and ERIC were consulted through OVID interface from their respective inceptions to November, 2020. Two reviewers independently selected studies, extracted data and assessed the risk of bias of studies using appropriate tools. We conducted data synthesis using a narrative form. GRADE was used for evaluating quality of cumulative evidence. RESULTS: In total, we included 12 studies with 38,732 participants from 6927 citations identified. Eleven of them were cross-sectional, and one was a cohort study with acceptable methodological quality. We found that: 1) family physicians with diverse clinical and nonclinical activities significantly improve their job satisfaction (p<0.05); 2) family physicians with a variety of clinical practices significantly improve their competences and health status (p<0.05); 3) family physicians who perform clinical procedures (mainly extended to gynecological procedures) significantly improve their psychosocial outcomes (e.g., job satisfaction) (p<0.05); and 4) some associations are not statistically significant (e.g., relation between variety of practice settings and outcomes). We observed that the evidence available has a very low level. CONCLUSIONS: Our findings suggest that the scope of practice may be favorably associated with some family physician outcomes but with a very low level of evidence available. Based on these findings, healthcare system managers could monitor the scope of practice among family physicians and encourage future research in this field. SYSTEMATIC REVIEW REGISTRATION: Our protocol was registered under the number CRD42019121990 in PROSPERO.